Legal Obstacles to Private Enforcement of Competition Law - Michal S. Gal; Rivi Dahan (Market and Competition Law Review)
Private enforcement of competition law serves many important goals, including deterrence of future anti-competitive harms and correction of past harms. This article sheds light on several potential legal obstacles to such enforcement which could prevent it from achieving its goals. The examples mainly build upon the experience of different jurisdictions with private litigation. It also suggests some possible solutions for dealing with or limiting such obstacles. As Europe is in the early stages of applying its Damages Directive and creating a private competition law enforcement regime, recognising – and possibly avoiding – obstacles to efficient private enforcement is both timely and important.